1997
DOI: 10.1093/milmed/162.10.695
|View full text |Cite
|
Sign up to set email alerts
|

Female United States Air Force Pilot Personality: The New Right Stuff

Abstract: With increasing numbers of female military pilots, it is important to understand the psychological and psychiatric gender differences of pilots. Using the "big five" personality structure (neuroticism, extraversion, openness to new experiences, agreeableness, and conscientiousness), female United States Air Force pilots were compared with both male Air Force pilots and to a female comparison group. Female Air Force pilots were higher on the Extraversion, Agreeableness, and Conscientiousness scales than male pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
1
17
1
1
Order By: Relevance
“…Different personality instruments have yielded results that can be confusing or difficult to interpret in relation to job performance, especially since these instruments were designed for a clinical population with psychopathology (Dolgin, Kay, Langelier, Wasel, & Hoffman, 2002;King, McGlohn, & Retzlaff, 1997;Retzlaff & Gibertini, 1987). Findings using the MMPI, for example, have proposed that aviators were social, hysteric, aggressive, selfconfident, and intellectually-striving (e.g., Culpepper, Jennings, & Perry, 1972).…”
Section: The Aviator Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different personality instruments have yielded results that can be confusing or difficult to interpret in relation to job performance, especially since these instruments were designed for a clinical population with psychopathology (Dolgin, Kay, Langelier, Wasel, & Hoffman, 2002;King, McGlohn, & Retzlaff, 1997;Retzlaff & Gibertini, 1987). Findings using the MMPI, for example, have proposed that aviators were social, hysteric, aggressive, selfconfident, and intellectually-striving (e.g., Culpepper, Jennings, & Perry, 1972).…”
Section: The Aviator Personalitymentioning
confidence: 99%
“…A bright spot in the research has been the creation of positive, performance-based measures, such as the NEO-PI-R, that have proven to be more accurate descriptors and predictors of personality (Dolgin et al, 2002;King, 1994;King et al, 1997). The NEO-PI-R is the most commonly used instrument measuring FFM factor and facet levels (Bernard & Walsh, 2004).…”
Section: Rationale For Using the Ffm In This Investigationmentioning
confidence: 99%
“…King, McGlohn and Retzlaff (1997) found that female Air Force pilots were lower on Openness than a comparison group of college students. In contrast, Johnson & Mclntyre (1998) found higher Openness for females than males in their sample of trainees at the Defense Equal Opportunity Management Institute (DEOMI) who were also members of the Armed Services.…”
Section: Gender Differences In Personalitymentioning
confidence: 88%
“…However, Lynn & Martin (1997) found that men obtained higher means than women on Extraversion across 30 countries. In a sample of United States Air Force pilots, King, McGlohn, & Retzlaff (1997) found that female pilots were higher on Extraversion than male pilots.…”
Section: Gender Differences In Personalitymentioning
confidence: 96%
“…DTIC is devoted primarily to military technical reports while the remaining databases report primarily refereed journal articles. Different personality instruments have yielded results that can be confusing or difficult to interpret in relation to job performance, especially since these instruments were designed for a clinical population with psychopathology (Callister, King, Retzlaff, & Marsh, 1997;Dolgin, Kay, Langelier, Wasel, & Hoffman, 2002;King, McGlohn, & Retzlaff, 1997;Retzlaff & Gibertini, 1987). Studies using the NEO-PI-R have proven to be more helpful in identifying the personality traits of aviators.…”
Section: Introductionmentioning
confidence: 99%